2021
DOI: 10.3897/natureconservation.43.58997
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of climate change on future freshwater fish diversity at global scale

Abstract: The aim of the present study was to predict future changes in biodiversity attributes (richness, rarity, heterogeneity, evenness, functional diversity and taxonomic diversity) of freshwater fish species in river basins around the world, under different climate scenarios. To do this, we use a new methodological approach implemented within the ModestR software (NOO3D) which allows estimating simple species distribution predictions for future climatic scenarios. Data from 16,825 freshwater fish species were used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…For example, in Europe, sh species are at high risk of losing their potential habitat by 2050 (median loss: 43%), and 8 species will completely lose their ranges over time as a result of climate change 53 . Also, a global study of freshwater sh species showed that half of the current freshwater sh species can become extinct in the next few decades 54 . Finally, we found that some sensitive/endemic species are likely to disappear from Iranian waters, while other tolerant/resistant species are likely to expand their ranges, i.e., our sh fauna will become increasingly homogenous and less regionally diverse, as predicted in another study 55 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Europe, sh species are at high risk of losing their potential habitat by 2050 (median loss: 43%), and 8 species will completely lose their ranges over time as a result of climate change 53 . Also, a global study of freshwater sh species showed that half of the current freshwater sh species can become extinct in the next few decades 54 . Finally, we found that some sensitive/endemic species are likely to disappear from Iranian waters, while other tolerant/resistant species are likely to expand their ranges, i.e., our sh fauna will become increasingly homogenous and less regionally diverse, as predicted in another study 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Another anthropogenic change of global concern is the climate crisis, which is also likely to interact with both habitat degradation [6] and invasive species [33] and complicate their impacts e.g., [1,3,34]. South Africa, including redfin habitat, is no exception to the impacts of climate change, and tropical to sub-tropical, small-bodied fish with limited distributions, such as redfins, are particularly vulnerable to climate change effects [35]. Deeper water may act as a thermal refuge [36] and artificial refugia can mitigate some impacts of habitat destruction [6] and provide protection from invasive predators [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…This in turn impacts population replenishment and connectivity patterns of local and invasive fishes. Warmer temperatures modifies community structure and dynamics that in turn facilitate invasions (Robert et al, 2017;Manjarres-Hernandez et al, 2021;Arnaud et al, 2021). Invasion of non-native introduced fishes even in changing environments and climate exert their effects on new habitats consequently emerging as a major threat for ecosystems around the globe, partly with irreversible consequences for the local biota (Panlasigui et al, 2018).…”
Section: Discussionmentioning
confidence: 99%